Hubungan Penggunaan Gadget Dengan Perkembangan Emosional Pada Anak Usia Prasekolah di RA Karakter Assalam Manado - Sri Delviana Daud; Sri Wahyuni; Nelfa F. Takahepis (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
The excessive use of gadgets can be interfere in children's development, especially in preschool children. Children who are accustomed to overusing gadgets will have an impact on their emotional development. The aims of this study is to determine the relationship between gadgets uses on emotional development in preschool age children in RA Character Assalam Manado. This is analytical descriptive research method with the cross sectional design. The sample of respondents in this study was 52 people using Total Sampling. Data collection using questionnaire sheets. In analysis using Chi-Square with Continuity Correction α ≤ 0,05. Results of the study were obtained: Out of 52 there were 32 (61,5%) parents having children with good emotional development; 34 (65.4%) parent having children using gadgets with an abnormal duration (> 1 hour/day), There was a significant relationship between gadget use and emotional developments in preschool age children in RA Character Assalam Manado. The conclusion in this study; there is a relationship between gadgets use and emotional development in preschool children at RA Character Assalam Manado. Based on the results of the research, it is suggested the teachers at the school should be able to coordinate with the student parents to more understanding the impact of the gadget use on the children emotional development.